On multistage homotopy-perturbation method applied to nonlinear biochemical reaction model - Hashim, Ishak; Chowdhury, Md. Sazzad Hossien; Mawa, S. (Elsevier, 2008)
The total time evolution of the reactant concentrations in the basic enzyme-substrate reaction is simulated by an adaptation of the standard analytic homotopy-perturbation method (HPM). The standard HPM is converted into a hybrid numeric–analytic method called the multistage HPM (MHPM). The numerical results obtained from the MHPM and the classical fourth-order Runge–Kutta (RK4) method are in complete agreement.